Interacción y ensamblaje entre los habitantes de los barrios del Cabildo La Libertad – Sector La Colmena (Artículos de Investigación) - Torres, Sara (2019)
The term interaction has been widely studied by Erving Goffman and its main characteristic is that it occurs between two or more people in a reciprocal way and with an immediate influence. While the assembly is one of the basic concepts of the Theory of the actor-network, and that refers to the formation of networks of actors that interact with each other in order to achieve a particular purpose. The particularity of the assemblies is that they can be formed from one moment to another. Based on these two categories, a study was developed in the La Libertad-La Colmena to establish whether interaction and/or assemblies are carried out in the neighborhoods that comprise it. We worked on characterizing the participants of the meetings following around sex, age, means of communication of their preference, to give a more real form to the interactions and assemblies raised and thus be able to observe their similarities and differences.